2021
DOI: 10.1088/1361-665x/ac1f64
|View full text |Cite
|
Sign up to set email alerts
|

Effects of silica on mechanical and rheological properties of EPDM-based magnetorheological elastomers

Abstract: Magnetorheological elastomers (MREs) are a kind of emerged smart material, where its responsive moduli in terms of mechanical and rheological properties are largely influenced by the presence of an external magnetic field. However, the incompatibility on the surface properties of its raw materials (fillers and matrix) may deteriorate the required properties of MREs. Therefore, in this study, the innovation of MRE by embedding silica nanoparticles as an additive has been experimentally investigated to strengthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 39 publications
2
14
0
Order By: Relevance
“…Some unique phenomenon was observed in S1, as the interfacial defects clearly appeared after the temperature test [ 22 ]. Meanwhile, in S5 ( Figure 1 b), it is clearly observed that the CIPs and silica are embedded in the EPDM matrix, indicating a positive interfacial interactions between fillers and matrix [ 17 ]. In the meantime, some of the silica is adhered on the surface of CIPs and could be seen as a layer on the surface of CIP as seen in Figure 1 c. Basically, when the polymer is exposed to a high temperature (>50 °C), the molecules in the form of long polymer chains would vibrate and stretch, causing the chains to disentangle and slide more easily.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some unique phenomenon was observed in S1, as the interfacial defects clearly appeared after the temperature test [ 22 ]. Meanwhile, in S5 ( Figure 1 b), it is clearly observed that the CIPs and silica are embedded in the EPDM matrix, indicating a positive interfacial interactions between fillers and matrix [ 17 ]. In the meantime, some of the silica is adhered on the surface of CIPs and could be seen as a layer on the surface of CIP as seen in Figure 1 c. Basically, when the polymer is exposed to a high temperature (>50 °C), the molecules in the form of long polymer chains would vibrate and stretch, causing the chains to disentangle and slide more easily.…”
Section: Resultsmentioning
confidence: 99%
“…The values of elongation at break for the addition of 0, 3, 6, 9 and 11 wt.% were at 219.98%, 299.12%, 360.09%, 478.42% and 525.23%, respectively. This finding was mainly related to the adhesiveness of silica into CIPs that has improved the interfacial adhesion between fillers and matrix and enhanced the elasticity of the MRE [ 17 ]. The improved adhesion between fillers (CIPs and silica) and matrix has led to a better interaction on the surface of MRE because of the stress transfer between them.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A small value of H c indicates good soft magnetic properties, which are desirable in the fabrication of smart materials as the magnet is easily demagnetized after removing the magnetic field. It should be noted that sample 6 could represent all the Gr–MRP samples (samples 2, 3, 4, and 5) since the content of CIP was the same at 70% and a few studies [ 38 , 39 ] have shown that the Gr does not substantially influence the magnetic properties, especially M s . The magnetization saturation was therefore mostly determined by the CIP content of MRP and Gr–MRP samples.…”
Section: Resultsmentioning
confidence: 99%
“…Magnetorheological Elastomers (MREs) are one such smart material, which when subject to an external magnetic field tend to change their mechanical and rheological properties such as stiffness, natural frequency, and damping capacity [ 16 , 17 , 18 , 19 ]. The controllability of the mechanical and rheological properties of MRE makes them resilient over a wide range of disturbance frequencies [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%